Diversity of Anaplasmataceae Transmitted by Ticks (Ixodidae) and the First Molecular Evidence of Anaplasma phagocytophilum and Candidatus Anaplasma boleense in Paraguay - Salvioni Recalde, Oscar Daniel (2024)
Anaplasmataceae bacteria are emerging infectious agents transmitted by ticks. The aim of this study was to identify the molecular diversity of this bacterial family in ticks and hosts, both domestic and wild, as well as blood meal sources of free-living ticks in northeastern Paraguay. The bacteria were identified using PCR-HRM, a method optimized for this purpose, while the identification of ticks and their blood meal was performed using conventional PCR. All amplified products were subsequently sequenced. The bacteria detected in the blood hosts included Ehrlichia canis, Anaplasma platys, and Anaplasma phagocytophilum, Candidatus Anaplasma boleense, and Wolbachia spp., which had not been previously reported in the country. Free-living and parasitic ticks on dogs (Canis lupus familiaris) and wild armadillos (Dasypus novemcinctus) were collected and identified as Rhipicephalus sanguineus and Amblyomma spp. The species E. canis, A. platys, A. phagocytophilum, and Ca. A. boleense were detected in domestic dog ticks, and E. canis and A. platys were found for the first time in armadillos and free-living ticks. Blood feeding sources detected in free-living ticks were rodents, humans, armadillos and dogs. Results show a high diversity of tick-borne pathogens circulating among domestic and wild animals in the northeastern region of Paraguay.